Spectroscopy as a tool to detect multinuclear Cu(ii)–triethanolamine complexes in aqueous solution. Issue 11 (15th February 2018) - Lommens, Petra; Tack, Pieter; Vander Elst, Luce; Van Driessche, Isabel; Vincze, Laszlo; Sinnaeve, Davy
Abstract : The Evans method, Extended X-ray Absorption Fine Structure (EXAFS) and NMR relaxation dispersion (NMRD) spectroscopy were used to prove the existence of multimeric Cu(ii )–triethanolamine species in aqueous solutions. Abstract : Complexes of Cu(ii ) with triethanolamine (TEA) are widely used in aqueous precursor solutions of Cu-based catalysts and metal oxides such as YBa2 Cu3 O7− δ superconductors. An outstanding question is whether such complexes are multinuclear in solution. Here, we use various spectroscopic techniques to unmistakably prove the existence of such multimers. Firstly, we introduce an original approach based on NMR spectroscopy and the Evans method that establishes the existence of multimers in aqueous solution at pH 4 and higher, and allows precise monitoring of the formation of these complexes with increasing pH. Secondly, we use extended X-ray absorption fine structure (EXAFS) spectroscopy to show that a Cu–Cu interaction exists at pH 9.5, which is not observed in acidic (pH 2) solutions. Finally, NMRD measurements reveal additional structural information regarding the multinuclear complexes. Knowledge concerning the nature of Cu(ii )–TEA complexes in solution is of great relevance in view of the design of speciation models to predict the stability of copper triethanolamine-based precursor solutions.